Friction and wear properties of an automobile brake lining reinforced by lignin fiber and glass fiber. Issue 5 (4th September 2017) - Chengmin, Wang; Xuefeng, Yang; Xiguang, Cai; Tao, Ma; Yunxi, Li; Peilong, Song
Abstract : Purpose: This paper aims to thrash out friction and wear properties of automobile brake lining reinforced by lignin fiber and glass fiber in braking process. Design/methodology/approach: ABAQUS finite element software was used to analyze thermo-mechanical coupled field of friction materials. XD-MSM constant speed friction testing machine was used to test friction and wear properties of friction material. Worn surface morphology and mechanism of friction materials were observed by using scanning electron microscope. Findings: The results show that when the temperature was below 350°C, worn mechanism of MFBL was mainly fatigue wear and abrasive wear, and worn mechanism of GFBL was mainly fatigue wear because MFBL contained lignin fiber. Therefore, it exhibits better mechanical properties and friction and wear properties than those of GFBL. Originality/value: Lignin fiber can improve mechanical properties and friction and wear properties of the automobile brake lining.